Implementation of the Competency Certification Program as Effort to Improve the Quality of Vocational School Graduates - Anggraini, Septiana; Madhakomala, R; Listyasari, Winda Dewi; Huda, Syafaat Ariful (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to describe the implementation of the competency certification program in vocational high schools as a strategy to improve the quality of vocational education and strengthen alignment with industry demands. Methodology: The study uses a qualitative descriptive method supported by grandtour interviews with the Vice Principal for Curriculum as the key informant, along with documentation of LSP-P1 activities and institutional records analyzed through data reduction, data display, and conclusion drawing. Main Findings: The findings show that competency certification implementation includes program planning aligned with policies and industry needs, assessments conducted through LSP-P1, collaboration with business and industry partners, and strategies to address challenges related to assessor availability, facility limitations, and student readiness. The results indicate that certification enhances students’ employability, professionalism, and competitiveness. Novelty/Originality of this study: The novelty of this study lies in positioning LSP-P1 certification not merely as an administrative procedure but as a transformative instrument for strengthening the quality culture in vocational